An Investigation into the Conditions of ICT Application at the Teacher Education Institutions - Vannasouk Bouasangthong; Say Phonekeo; Sithane Soukhavong; Khamseng Thalungsy; Thongsay Phongphanit; Phonesy Vathana; Phoutsakhone Channgakham; Senglamphanh Dyvanhna; Khammeung Sybounheaung; Chintana Phengphilavong (Universitas Pendidikan Indonesia (UPI), 2024)
Information Communication Technology (ICT) has become an indispensable part of teachers in most countries in the world to keep up with the needs of learning and teaching. This paper aims at investigating the conditions of using ICT, exploring the need for ICT training, and examining the guidelines for developing ICT works in the Lao teacher education institutions, Lao PDR. The sample group for this research was 460 teachers and 32 administrators from 16 teacher education institutions throughout Lao PDR. The questionnaire and semi-structured interviews were employed to collect the data. The data were analyzed by using descriptive statistics for the quantitative data and the thematic and content analysis was used for the qualitative data. The findings reveal that the overall conditions of ICT application were at a moderate level in terms of the ICT Infrastructure, ICT facilities, and ICT personnel. The needs for ICT training range from how to use applications to using software for data analysis. The guidelines and suggestions for developing ICT works include: encouraging teachers to undertake ICT, conducting ICT professional training, providing sufficient financial support, supporting ICT facilities/tools, creating ICT resource rooms, and inspecting and monitoring the ICT integration of the teachers. It is recommended that regular support and training from related stakeholders, ICT can be best facilitated and fostered in the Lao teacher education institutions to provide a high-quality education in the new era.